DESIGN OF ROBUST NAVIGATION AND STABILIZATION LOOPS OF PRECISION ATTITUDE AND HEADING REFERENCE SYSTEM - Sushchenko, Olha (Proceedings of National Aviation University (archive), 2017)
Purpose: The paper focuses on problems of design of robust precision attitude and heading reference systems, which can be applied in navigation of marine vehicles. The main goal is to create the optimization procedures for design of navigation and stabilization loops of the multimode gimballed system. The optimization procedure of the navigation loop design is based on the parametric robust H2/H∞-optimization. The optimization procedure of the stabilization loop design is based on the robust structural H∞-synthesis. Methods: To solve the given problem the methods of the robust control system theory and optimization methods are used. Results: The kinematical scheme of the precision gimballed attitude and heading reference system is represented. The parametrical optimization algorithm taking into consideration features of the researched system is given. Method of the mixed sensitivity relative to the researched system design is analyzed. Coefficients of the control laws of navigation loops are obtained based on optimization procedure providing compromise between accuracy and robustness. The robust controller of the stabilization loop was developed based on robust structural synthesis using method of the mixed sensitivity. Simulation of navigation and stabilization processes is carried out. Conclusions: The represented results prove efficiency of the proposed procedures, which can be useful for design of precision navigation systems of the moving vehicles.